2011
DOI: 10.4314/afrrev.v5i6.17
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray of the Level of Electronic Purse Usage in Nigeria

Abstract: This study sets out to examine the level of e-purse usage in Nigeria. Despite the invasion of e-purse as electronic banking channels that has the potential of disempowering the cash systems of exchange and granting firms competitive edge, it is interesting to note that the rate of cash usage still dominates in the Nigeria society. Thus, when compared with more advanced countries, less technically developed nations like Nigeria tend to be backward in terms of e-purse adoption and usage. The study results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Even within the existing bank customers, there are equally some customers who may not be willing to adopt the innovation for fear of insecurity, high risk perception, inertia, lack of trust, low compatibility and high level of complexity. Ogbuji et al (2011) found that insecurity, illiteracy and customer inertia are the key causes of low acceptance and usage rate of e-purse in Nigeria. Wai-Ching (2007) found that security concerns is one of the factors that play an important part in determining the users' acceptance of e-banking services with respect to different segmentation of age group, education and income level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even within the existing bank customers, there are equally some customers who may not be willing to adopt the innovation for fear of insecurity, high risk perception, inertia, lack of trust, low compatibility and high level of complexity. Ogbuji et al (2011) found that insecurity, illiteracy and customer inertia are the key causes of low acceptance and usage rate of e-purse in Nigeria. Wai-Ching (2007) found that security concerns is one of the factors that play an important part in determining the users' acceptance of e-banking services with respect to different segmentation of age group, education and income level.…”
Section: Discussionmentioning
confidence: 99%
“…Since inertia reflects customers' reluctance towards trying alternative products and services, some research efforts in the academic literature have been devoted to examining the determinants of this reluctance even in the face of dissatisfaction. Ogbuji et al (2011) argued that insecurity of electronic transactions is one of the root causes of customer inertia towards e-purse acceptance and usage. Customers' ignorance or absolute absence of alternative products or services can equally play a part.…”
Section: Consumers' Attitude Towards Innovationmentioning
confidence: 99%
See 1 more Smart Citation